A Measurement Method to Determine the Working Length of the Arm in Torque Standard Machine - Vu, Van Duy; Vu, Toan Thang; Vu, Khanh Xuan (Old Journal, 2017)
Torque is one of the derived quantities in the International Measurement Units System (SI), which is used more and more with industrial developing. The measurement accuracy of torque quantity depends on three main factors: accuracy of the working length of the arm, the uncertainty of the acting force, the friction torque of the bearing, etc. In the world, some countries have their primary torque standard machines to calibrate and compare torque standards and measuring equipment. This article introduces the measurement method for accurate determining the working length of the arm in a torque standard machine, and to contribute to improving the accuracy of the torque standard machines.